Karakteristik Kimia dan Sensori Minuman Serbuk Instan Daun Saga (Abrus precatorius L.) Dengan Variasi Konsentrasi Sukrosa Dan Maltodekstrin - Rohmayanti, Titi; Ulfah, Luthfia; Nurlaela, Raden Siti (Universitas Djuanda, 2023)
Instant saga leaf powder drink with a ratio of sucrose and maltodextrin concentrations is a form of utilizing the saga leaf plant as an ingredient for making instant powder drinks. This research aims to study the effect of the comparison of sucrose and maltodextrin concentrations. The research was conducted using a Completely Randomized Design (CRD) with 1 factor, namely the influence of sucrose concentration: maltodextrin concentration with 4 treatment levels A1 (100%: 0%), A2 (85%: 15%), A3 (65%: 35%), A4 (50%:50%) and 2 repetitions. The data analysis used was ANOVA with Duncan's Advanced Test (α=0.05). Product analysis includes tests for water content, ash content, sucrose content, reducing sugar, solubility, total dissolved solids and organoleptics including color, aroma, taste1, taste2, viscosity and overall parameters. Determination of selected products is based on chemical tests according to SNI and organoleptic (sensory and hedonic). The research results showed that the selected product for instant saga leaf powder drink was A2 treatment with a sucrose and maltodextrin concentration ratio of 85%:15% and antioxidant analysis was carried out. The chemical analysis produced by the selected product was found to have a water content of 2.09%, ash content of 0.62%, sucrose content of 37.84%, reagent sugar of 4.93%, solubility of 97%, total dissolved solids of 19.15⸰Brix and antioxidant IC50 118.11 ppm in the medium category.